2013
DOI: 10.1016/j.jcjd.2013.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Glycemic Control

Abstract: Glycated hemoglobin (A1C) is a valuable indicator of treatment effectiveness and should be measured every 3 months when glycemic targets are not being met and when diabetes therapy is being adjusted. Awareness of both measures of glycemia, self-monitoring of blood glucose (SMBG) results and A1C, provide the best information to assess glycemic control. SMBG should not be viewed as an intervention but rather as an aid to assess interventions and hypoglycemia.Timing and frequency of SMBG should be determined indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…An HbA1c “A1C Now+”™ point-of-care assay provided quantitative measurement of the % of glycated haemoglobin over the last 3 months. The average level of blood glucose in the 30 days immediately preceding the blood sample contributes ~50% of the HbA1c results whereas ~10% is from the past 90–120 days [18,19]. The accuracy of the A1C Now+ was tested on participants who were diabetic and non-diabetic (n=189) in a multiple-site study conducted in the USA, with a 99% accuracy rate found when compared to the National Glycohemoglobin Standardization Program reference results [20].…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…An HbA1c “A1C Now+”™ point-of-care assay provided quantitative measurement of the % of glycated haemoglobin over the last 3 months. The average level of blood glucose in the 30 days immediately preceding the blood sample contributes ~50% of the HbA1c results whereas ~10% is from the past 90–120 days [18,19]. The accuracy of the A1C Now+ was tested on participants who were diabetic and non-diabetic (n=189) in a multiple-site study conducted in the USA, with a 99% accuracy rate found when compared to the National Glycohemoglobin Standardization Program reference results [20].…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Although we have evidence-based guideline recommendations to help support many of these educational activities, clinician opinions may also influence the advice we provide. 2,3,12,16 For example, clinicians often believe that fear of injections are a critical barrier to introducing insulin in patients with type 2 diabetes and, therefore, may delay introducing this therapeutic alternative. 12,16 However, patients appear to rate other concerns, like addiction to insulin, the complexity of insulin regimens, and perceived restrictions on lifestyle, as more important compared to the fear of injection pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists who have active diabetes practices lead these sessions and the content is consistent with current guideline recommendations and training material provided to patients who are starting insulin. 3,14,15 The session runs for 50 minutes with a ratio of 8 students to 1 pharmacist in each session. Students are encouraged to attempt at least one blood glucose check and mock insulin injection while they are directly supervised by the pharmacists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that diabetes-related complications are prevented by selfmanagement that constitute health-related behavior change (Berard et al, 2013;Chlebowy & Garvin, 2006;Komar-Samardzija, Braun, Keithley, & Quinn, 2012), which enables persons with T2D to control their disease (Haas et al, 2013).…”
Section: Marital Statusmentioning
confidence: 99%